Safety of Antibiotics in Hospitalized Children in Romania: A Prospective Observational Study - Noémi-Beátrix Bulik; Andreea Farcaș; Camelia Bucșa; Irina Iaru; Ovidiu Oniga (MDPI AG, 2022)
Antibiotics are among the most prescribed drugs in pediatric inpatients and are frequently associated with adverse drug reactions (ADRs) in children. This study aimed to assess the frequency and type of ADRs related to the use of antibiotics in pediatric inpatients through a prospective observational study, conducted over 6 months, covering the winter and spring seasons when the incidence of infections peaks in Romania. ADRs were evaluated for causality, avoidability and severity. Among the 266 included children, 25 (9.4%) experienced 30 ADRs. ADR frequency tended to be higher in ≤2-year-olds (13 of 25, 52.0%) than in other age categories. Gastrointestinal and hematological ADRs were most frequently observed. Diarrhea was the most common ADR associated with antibiotics (8 of 30, 26.7%). Ceftriaxone (16 of 30, 53.3%), cefuroxime, ceftazidime and azithromycin (3 of 30, 10.0% each) were most commonly responsible for ADRs. After causality assessment, 2 (6.7%) ADRs were considered definite, 12 (40.0%) probable and 16 (53.3%) possible. One ADR was classified as definitely avoidable and one as possibly avoidable. Seven children required treatment for ADRs. Antibiotic treatment was discontinued in 4 children. Antibiotics frequently caused ADRs in ≤ 2-year-olds and were commonly associated with gastrointestinal symptoms. Close monitoring of antibiotic-associated ADRs remains important in the pediatric population.